The library PR handbook high-impact communications - Gould, Mark R. (IG library, 2009)
The fast-paced and complex PR role is becoming increasingly important as libraries need to respond quickly to the changing media landscape and the country's demographic shifts. This handbook will get you on the right PR track with: ideas to harness a celebrity brand and create effective public service announcements; the how-tos of amplifying your message through partnerships; the means to develop affordable podcasts, savvy outreach programs, and special events; and tips for using gaming to build excitement. Written by high-profile experts in the PR field, "The Library PR Handbook" is the essential reader for those looking to spice up their library's message and get the word out.